Physiological response to bouts of high intensity exercise two hours apart - Thompson, K. G.; Harrison, A.; Dietzig, B.; Cosgrove, M.; Hardman, S. (Journal of Human Movement Studies, 2006)
Athletes in high-intensity exercise events may have to compete twice vvithin a few hours (e.g. the heats and finals of championships/ events). Although evidence suggests maximal performance is reproducible, there are few data shovving whether physiological responses vvould remain the same or demonstrate an additive effect. Such knowledge would influence scientific and coaching support to athletes in terms of their physical preparation and tactical considerations. The aim of this study was to investigate the physiological response to a 30s bout of maximal exercise completed on two occasions, two hours apart. Following a standardised warm-up, nine highly-trained males undertook a 30s Wingate test. Two hours later the test was repeated. Serum ammonia was significantly greater after the first trial compared to the second trial (p=0.001) despite no differences in mean power Output, peak power Output and time to peak power. No significant differences were found between trial s for other physiological parameters. Two hours rest allowed for the normalisation of a wide ränge of physiological responses and subsequently a similar response to another bout of exercise. The difference in serum ammonia between trials may reflect an overshoot in muscle creatine phosphate restoration.